The Effect of Profitability and Liquidity on Going Concern Audit Opinion Acceptance: The Role of Audit Committee - Jasman; Khairani Shafira (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this study was to determine the effect of profitability and liquidity ongoing concern audit opinion acceptance by using the audit committee variable as a moderator. The data in this study uses secondary data in the form of financial reports available on the Indonesia Stock Exchange (IDX) website. The population of this study are customer cyclical companies listed on the IDX for the period 2019 - 2021, with a total sample size of 64 cyclical customer companies. Based on the results of this study, profitability influences the acceptance of going concern audit opinion on companies. Meanwhile, liquidity does not influence going concern audit opinion acceptance. The audit committee is also unable to moderate the effect of profitability and liquidity ongoing concern audit opinion acceptance